2013
DOI: 10.3389/fnhum.2013.00602
|View full text |Cite
|
Sign up to set email alerts
|

The effect of transcranial direct current stimulation: a role for cortical excitation/inhibition balance?

Abstract: Transcranial direct current stimulation (tDCS) is a promising tool for cognitive enhancement and neurorehabilitation in clinical disorders in both cognitive and clinical domains (e.g., chronic pain, tinnitus). Here we suggest the potential role of tDCS in modulating cortical excitation/inhibition (E/I) balance and thereby inducing improvements. We suggest that part of the mechanism of action of tDCS can be explained by non-invasive modulations of the E/I balance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
191
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(211 citation statements)
references
References 53 publications
18
191
1
1
Order By: Relevance
“…As noted in the Introduction, it has recently been suggested that interindividual variability in stimulation effects is at least in part related to interindividual variability in the balance between cortical excitation and inhibition (Krause et al, 2013) and that this balance modulates the effect of tDCS in a nonlinear fashion. Specifically, the relation between the excitation-inhibition balance within a brain area on the one hand, and its efficiency on the other, is suggested to follow an inverted-U shape in which optimal performance is achieved when excitation and inhibition interact in a way that permits both flexibility and stability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As noted in the Introduction, it has recently been suggested that interindividual variability in stimulation effects is at least in part related to interindividual variability in the balance between cortical excitation and inhibition (Krause et al, 2013) and that this balance modulates the effect of tDCS in a nonlinear fashion. Specifically, the relation between the excitation-inhibition balance within a brain area on the one hand, and its efficiency on the other, is suggested to follow an inverted-U shape in which optimal performance is achieved when excitation and inhibition interact in a way that permits both flexibility and stability.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these immediate effects, long-term effects of up to 1.5 hr after stimulation have been shown for stimulation durations of 9 min and longer in the motor domain (Nitsche & Paulus, 2001). Recent work furthermore suggests that stimulation effects on performance are at least in part determined by the preexisting balance between cortical excitation and inhibition (Krause & Cohen Kadosh, 2014;Krause, Márquez-Ruiz, & Cohen Kadosh, 2013). The relation between the excitationinhibition balance within a brain area and its efficiency is argued to follow an inverted-U shape in which functioning is optimal when excitation and inhibition interact in a way that permits both flexibility (i.e., plasticity, new learning) and stability (i.e., resistance to distraction, maintenance of information).…”
Section: Introductionmentioning
confidence: 99%
“…Many factors could play a role here, ranging from differences in head and brain anatomy to gender and genetics (see Li et al (2015b) and Krause and Cohen Kadosh (2014) for reviews). Differences in baseline brain state and cortical excitation/inhibition balance seem especially relevant (Krause et al 2013), as they could explain why in some studies the effects of stimulation were contingent on baseline task performance (e.g., Learmonth et al 2015;Benwell et al 2015;London and Slagter 2015).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been proposed that an optimal balance of excitation/inhibition in different cortical regions promotes optimal cognitive functioning. Therefore, tDCS may exert different and sometimes contradictory effects in populations that vary with respect to this balance, such as those with attention deficit hyperactivity disorder or depression (Krause, Marquez-Ruiz, & Cohen Kadosh, 2013). Furthermore, genetic factors (Brunoni et al, 2013;Plewnia et al, 2013) and anatomical differences that impact the electric field generated by tDCS may also influence the response to stimulation.…”
Section: Baseline Performance and Other Individual Difference Factorsmentioning
confidence: 99%